Intellectual Capital, Board Diversity, and Firms’ Financial Performance: A Complex System Perspective - Yu Gao; Xinyu Tian; Jian Xu (Systems)
The objective of this study is to analyze the impact of intellectual capital (IC) and its components on firm financial performance using data from Chinese agricultural listed companies during 2015–2020. The moderating role of board diversity in the relationship between IC and firm financial performance is also tested. The modified value-added intellectual coefficient (MVAIC) model is used to measure IC, and board diversity is measured by several indicators, such as diversity in gender, experience, professional background, and educational background. The results suggest that the overall IC and only one element (human capital) positively influence firm financial performance. Diversity in gender, professional background, and educational background positively moderate the relationship between IC and financial performance, while experience diversity has a negative moderating effect. Among IC components, experience diversity, and educational background diversity negatively moderate the relationship between human capital and financial performance. In addition, gender diversity and experience diversity have a negative moderating effect on the relationship between physical capital and financial performance, while professional background diversity and educational background diversity have a positive moderating effect. This study can provide some new insights for managers to devise strategies to improve IC performance and strengthen corporate governance in order to achieve sustainable development of the agricultural industry. It also can guide policymakers in making policies to improve IC efficiency and firm performance.